Fundamentos teóricos-metodológicos que caracterizan la intervención profesional de los trabajadores sociales en al ciudad de Trujillo - 2016 - Alza Salvatierra, Vanessa Jocelyn (2017)
ABSTRACT The present research is a descriptive type that seeks to know the theoretical and methodological foundations that characterize the professional intervention of social workers in the city of Trujillo during the year 2016. The study was carried out with a total of 36 social workers working in the city of Trujillo, working in the fields of health, education, welfare, business, justice, NGOs, and regional and local governments. The methods have been used: ethnographic, inductive-deductive, synthetic and techniques of observation, interview and survey. From the results obtained, we can affirm that the professional intervention of social workers is characterized by a positive influence, empiricist and pragmatist approach that has accentuated the separation between science and technique, theory and practice, methodology of knowledge and methodology of action.